2011
DOI: 10.4061/2011/850568
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Study of Blood Parasites in Rice Field Frogs,Hoplobatrachus rugulosus(Wiegmann, 1834)

Abstract: One hundred and forty adult rice field frogs, Hoplobatrachus rugulosus (Wiegmann, 1834), were collected in Srakaew province, Thailand. For blood parasite examination, thin blood smears were made and routinely stained with Giemsa. The results showed that 70% of the frogs (98/140) were infected with 5 species of blood parasites, including a Trypanosoma rotatorium-like organism, Trypanosoma chattoni, Hepatozoon sp. a, Hepatozoon sp. b, and Lankesterella minima. Pathological examination of the liver, lung, spleen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…in Lithobates clamitans (Ranidae) is benign or undetectable to the immune system. In contrast, Sailasuta et al (2011) show an infection by two morphotypes of Hepatozoon sp. caused pathological lesions with subacute to chronic inflammation in the liver of Hoplobatrachus rugulosus (Dicroglossidae).…”
Section: Discussionmentioning
confidence: 92%
“…in Lithobates clamitans (Ranidae) is benign or undetectable to the immune system. In contrast, Sailasuta et al (2011) show an infection by two morphotypes of Hepatozoon sp. caused pathological lesions with subacute to chronic inflammation in the liver of Hoplobatrachus rugulosus (Dicroglossidae).…”
Section: Discussionmentioning
confidence: 92%
“…Trypomastigotes of both species, however, have large size and this new species thus becomes a new member of the giant trypanosomes that includes species such as Trypanosoma mega , T. ranarum and T. rotatorium ( Martin et al., 2002 ). Despite the widespread distribution of T. chattoni including Asia (China, Werner, 1993 ; Kyushu and Ryukyu Islands, Miyata, 1978 ; Thailand, Sailasuta et al., 2011 ), North America (United Sates, Diamond, 1965 ; Canada, Jones and Woo, 1986 ) and South America (Brazil, Lemos et al., 2008 ), this species is monomorphic with little geographic variation. Both T. chattoni and T. tungarae n. sp.…”
Section: Resultsmentioning
confidence: 99%
“…UKM Danau golf club anurans had the most haemoparasite groups compared to Jeriau river and Fraser's hill golf course. The haemoparasites present in Sailasuta et al (2011) in their study conducted in Thailand. A previous study by Muhammad et al (2013) conducted in Malaysia found only two groups of parasites: Trypanosoma and Lankesterella, while another study also conducted in Malaysia but in other locations reported presence of five groups of haemoparasites (Rahman and Shakinah, 2015).…”
Section: Resultsmentioning
confidence: 97%